2020
DOI: 10.1111/jam.14674
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol efficacy of Trichoderma asperellum ‐enriched coconut fibre against Fusarium wilts of cherry tomato

Abstract: Aims Agro‐based wastes were evaluated as a medium for mass micropropagule production and optimal efficacy of Trichoderma asperellum B1092 in controlling Fusarium oxysporum f. sp. lycopersici and promoting tomato growth. This study focused on biological control because pathogen persistence in the soil makes the disease difficult to control. Methods and Results Rice bran, biochar, empty fruit bunches, coconut fibres, compost, top soil and mixed soil were evaluated as media for mass multiplication of T. asperellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This corresponds with our findings where tomato plants treated with T. viride and T. harzianum exhibited increased levels of proline. Similarly, Zehra et al (2017) reported elevated proline content and both Molla et al (2012) and Hasan et al (2020) found increased lycopene content in FOL infected tomato plants treated with T. harzianum. An increase in vitamin C in tomato was also reported by Li et al (2017)…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This corresponds with our findings where tomato plants treated with T. viride and T. harzianum exhibited increased levels of proline. Similarly, Zehra et al (2017) reported elevated proline content and both Molla et al (2012) and Hasan et al (2020) found increased lycopene content in FOL infected tomato plants treated with T. harzianum. An increase in vitamin C in tomato was also reported by Li et al (2017)…”
Section: Discussionmentioning
confidence: 82%
“…Tomato plants treated with T. viride and T. harzianum showed improved net photosynthetic rates (P N ), stomatal conductance (g s ) and transpiration rates (E) when compared to the untreated control. Hasan et al (2020) found that Trichoderma spp. increased the net photosynthetic rate (P N ), stomatal conductance (g s ) and transpiration rates (E) in cherry tomato plants in comparison to FOL infested plants.…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma species are vital in suppressing plant pathogen and facilitating plant growth in the agroecosystem ( Vinale et al, 2008 ; Contreras-Cornejo et al, 2016 ). The dramatic increase in the relative abundance of Trichoderma in AR was mainly attributed to the increase of two species, T. asperellum and T. virens , both of which can protect plant from Fusarium wilt ( Jogaiah et al, 2018 ; Hasan et al, 2020 ). In addition, endophytes of the genus Acremonium are resistant to herbivores and nematodes ( West et al, 1988 ; Breen, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a formulation of T. asperellum in coconut fiber promoted the growth of tomato plants and conferred resistance against F. oxusporum f.sp. lycopersici in field trials [ 226 ]. T. harzianum grown on a spent mushroom substrate (SMS) of Pleurotus ostreatus showed growth promotion in tomato plants and increased disease resistance against F. oxysporum f.sp.…”
Section: Trichoderma Bioformulations In Agriculture For Use ...mentioning
confidence: 99%